Effect of weather on leaf blast incidence in rice and predicting potential epidemics under various climate change scenarios - Aswathi N R (Academy of Climate Change Education and Research, 2016)
The rate of global warming is expected to continue increasing if no mitigation efforts take place to reduce the carbon intensity of the world economy and the consequent emission of green-house gases (Raupach et al., 2007). Agricultural production, and thus global food security, is directly affected by global warming (Ainsworth and Ort, 2010). Rice production plays an essential role in feeding the world’s population and will continue to be in the future, because rice is the most important global staple food in many countries. The production of rice, along with other agricultural crops, will be impacted by climate change. There is still great uncertainty about how climatic and atmospheric changes will affect the future productivity of food crops. Major future impacts of climate change are expected on food security and agricultural incomes, including shifts in production areas across the world. In addition to affecting rice production, climate change may alter pathogen dissemination and development rates, and modify the resistance, growth and metabolism of host plants. The geographical distributions of pathogens are very likely to change, and losses can be expected, in part due to altered effectiveness of control strategies. Thus climate change is a serious threat to agriculture because it can lead to significant changes in the occurrence and severity of plant diseases. All phases of the disease cycle, from the germination of spores to the development of lesions, are considerably influenced by climatic factors. The most important climatic factors are temperature and precipitation. These factors may be modified by the coming climate changes. Recent research indicates that the monsoon has changed in two significant ways during the past half-century: it has weakened (less total rainfall during June– September; Ramanathan et al. 2005; Dash et al. 2007), and the distribution of rainfall within the monsoon season has become more extreme (Goswami et al. 2006; Dash et al. 2009). Rice blast caused by Pyricularia oryzae an important disease of rice worldwide is known to cause severe yield losses in rice production area where high inputs of nitrogen fertilizer and favourable climatic conditions occur. Sometimes the yield losses reach as high as 50% in upland cultivations. Objectives of the study were to Study the effect of various weather parameters and climate change on incidence and development of leaf blast disease of rice and evaluation of disease forecasting models for leaf blast of rice. The field experiments were conducted during May 2016 to October 2016 at the Regional Agricultural Research Station of the Kerala Agricultural University at Pattambi, Palakkad district, Kerala. Crops sowing June showed a higher disease incidence compared to other dates of sowing. It was also noticed that variety Kanchana is more susceptible to Leaf blast incidence compared to Jyothi. The effect of weather on LAI significantly varied with varieties. The effect of weather on grain yield was significant. Under upland condition the sheath blight disease incidence was not observed even after artificial inoculation.The effects of weather and varieties on leaf blast incubation period were significant. EPRICE model developed by Savary et al., (2012) was used to forecast the disease severity of leaf blast disease in rice after transplanting. The model works on daily weather parameters particularly rainfall, maximum and minimum temperature, morning and afternoon relative humidity. RMSE for Kanchana prediction is 0.265. This shows that the predicted leaf blast severity was in good agreement with the observed values. So this model can be used for forecasting the rice blast severity under Kerala conditions. The future climatic projections have taken from Ensemble of 17 General Circulation Models (GCMs). The future carbon dioxide concentrations and climate data has been incorporated into disease simulation model-EPIRICE and predicted the future disease incidence possibility of blast for the years 2030, 2050 and 2080 in all the 14 districts of Kerala. The climate data for the years 2030, 2050 and 2080 under different RCPs. The impact of climate change on leaf blast severity in the various districts of Kerala showed a varying trend. Except in the northern districts (Malappuram, Wayanad, Kannur and Kasaragod) the disease severity showed a decreasing trend.